Sensitivity and specificity of simple erythrocyte osmotic fragility test for screening of alpha-thalassemia-1 and beta-thalassemia trait in pregnant women - Fuanglada Tongprasert (2018)
Aims: To evaluate the validity of new simple qualitative osmotic fragility test (simple OF) as a screening test in predicting thalassemia trait (alpha-thalassemia-1 and beta-thalassemia). Methods: This diagnostic test study was conducted on non-anemic pregnant women attending antenatal care clinic, Maharaj Nakorn Chiang Mai Hospital, during September 2007, and June 2008. Blood samples were collected from 477 singleton pregnancies with no obvious medical complication such as iron deficiency anemia. Simple OF was performed in the same day, using 0.45% glycerin saline solution instead of saline solution. Quantitative HbA2 test and PCR (SEA type) were performed as gold standard to confirm the diagnosis of beta-thalassemia trait and alpha-thalassemia-1 trait, respectively. The main outcome measures included sensitivity, specificity, positive and negative predictive value of simple OF. Results: The simple OF test had very high sensitivity of 100%, specificity of 73%, positive and negative predictive value of 35, and 100%, respectively. Conclusion: The new simple OF test (using 0.45% glycerin) has high sensitivity in detection of alpha-thalassemia-1 trait or beta-thalassemia trait and due to its simplicity, rapidity, availability and very low cost it may, therefore, be considered as a screening test in a large-scale population. © 2010 S. Karger AG, Base.